Treatment With Suboptimal Dose of Benznidazole Mitigates Immune Response Molecular Pathways in Mice With Chronic Chagas Cardiomyopathy - Farani, Priscila Silva Grijó; Begum, Khodeza; Vilar-Pereira, Glaucia; Pereira, Isabela Resende; Almeida, Igor C.; Roy, Sourav; Lannes-Vieira, Joseli; Moreira, Otacilio Cruz (Frontiers in Cellular and Infection Microbiology, 2021)
Chronic Chagas cardiomyopathy (CCC) is the most frequent and severe form of Chagas disease, a neglected tropical illness caused by the protozoan Trypanosoma cruzi, and the main cause of morbimortality from cardiovascular problems in endemic areas. Although efforts have been made to understand the signaling pathways and molecular mechanisms underlying CCC, the immunological signaling pathways regulated by the etiological treatment with benznidazole (Bz) has not been reported. In experimental CCC, Bz combined with the hemorheological and immunoregulatory agent pentoxifylline (PTX) has beneficial effects on CCC. To explore the molecular mechanisms of Bz or Bz+PTX therapeutic strategies, C57BL/6 mice chronically infected with the T. cruzi Colombian strain (discrete typing unit TcI) and showing electrocardiographic abnormalities were submitted to suboptimal dose of Bz or Bz+PTX from 120 to 150 days postinfection. Electrocardiographic alterations, such as prolonged corrected QT interval and heart parasite load, were beneficially impacted by Bz and Bz+PTX. RT-qPCR TaqMan array was used to evaluate the expression of 92 genes related to the immune response in RNA extracted from heart tissues. In comparison with non-infected mice, 30 genes were upregulated, and 31 were downregulated in infected mice. Particularly, infection upregulated the cytokines IFN-γ, IL-12b, and IL-2 (126-, 44-, and 18-fold change, respectively) and the T-cell chemoattractants CCL3 and CCL5 (23- and 16-fold change, respectively). Bz therapy restored the expression of genes related to inflammatory response, cellular development, growth, and proliferation, and tissue development pathways, most probably linked to the cardiac remodeling processes inherent to CCC, thus mitigating the Th1-driven response found in vehicle-treated infected mice. The combined Bz+PTX therapy revealed pathways related to the modulation of cell death and survival, and organismal survival, supporting that this strategy may mitigate the progression of CCC. Altogether, our results contribute to the better understanding of the molecular mechanisms of the immune response in the heart tissue in chronic Chagas disease and reinforce that parasite persistence and dysregulated immune response underpin CCC severity. Therefore, Bz and Bz+PTX chemotherapies emerge as tools to interfere in these pathways aiming to improve CCC prognosis.